Composición química y perfil de ácidos grasos de la carne de ñandú (Rhea americana) - Romanelli, Pedro Fernando [UNESP]; Trabuco, Elizeu [UNESP]; Scriboni, Andréia Borges [UNESP]; Visentainer, Jesuí Vergílio [UNESP]; Souza, Nilson Evelázio de [UNESP] (My University, 2008)
The purpose of this work was to determine the proximate composition and fatty acid profiles of the Gastrocnemius pars interna intramuscular fat (IMF) of rhea (Rhea americana) thighs. The birds were bred in captivity, fed with balanced feed (Nutriavestruz Crescimento - Purina) and kept in a pen with grass ad lib. The birds of both sexes used in the research weighed 23 kg on average and were aged about twelve (12) months old. They were subjected to hydric diet (12 h) before slaughtering by electric shock. The rhea meat showed an average moisture, protein, ash and total lipid contents of 74.1%, 22.8%, 1.5% and 1.6%, respectively. It was noticed the predominance of monounsaturated fatty acids (MUFA) in intramuscular fat (IMF), 42.3% and a high percentage of polyunsaturated fatty acids (PUFA), 29.7%.. The fatty acids found in higher proportion in rhea IMF were: 18:2n-6 (24.33%), 18:1n-9 (19.25%), 16:0 (13.70%), 22:1n9 (11.40%), 18:0 (10.66%), 15:1n-10 (8.62%), 24:1n-9 (2.90%) and 20:4n-6 (1.72%). The PUFA/SFA and n-6/n-3 ratios were 1.06 and 31.30, respectively. The consumption of rhea meat is a healthy alternative to red meat as it points to a lower susceptibility to cardiovascular diseases caused by the high consumption of fat comparatively to the consumption of meat from most domesticated animals. © 2009 Archivos Latinoamericanos de Nutrición.
Chemical composition and fatty acid profile of rhea (Rhea americana) meat
Keywords: Fatty acid profile; Ratite; Rhea; Rhea americana